Low-shrinkage all-solid waste concrete and preparation method thereof

By using the "internal curing" effect of titanium slag aggregate in solid waste-based concrete and the alkali-sulfate synergistic effect of calcium carbide slag and gypsum, the problems of large shrinkage and poor volume stability of solid waste-based concrete are solved, and the problem of solid waste-based concrete is achieved. Preparation of all solid waste concrete with low shrinkage, high strength and low carbon.

CN119390418APending Publication Date: 2025-02-07SICHUAN HUASHI GREEN HOMELAND BUILDING MATERIALS
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411508708.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When existing solid waste-based concrete reduces the amount of cement and realizes the resource utilization of solid waste, there are problems such as large shrinkage, poor volume stability, and alkali-returning and frost.

Method used

The "internal curing" effect of titanium slag aggregate is used, combining the high alkalinity of calcium carbide slag and the high sulfate content of gypsum, and the activity of water-quenched slag powder and other materials is stimulated through the coordinated excitation of alkali-sulfate, which can stimulate the activity of water-quenched slag powder to prepare low shrinkage All solid waste concrete does not use steel slag to avoid volume stability problems.

Benefits of technology

It realizes the advantages of reducing the drying and shrinking of concrete without using cement and chemical excitants, improving the strength and volume stability of concrete, and has the advantages of low carbon, green and economicality.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses low-shrinkage all-solid waste concrete and a preparation method thereof. The low-shrinkage all-solid waste concrete is prepared from the following raw materials in parts by mass: 14 to 20 parts of solid waste-based cementing material, 25 to 40 parts of high-titanium heavy slag sand, 35 to 50 parts of high-titanium heavy slag gravel, 5.5 to 7.5 parts of water and 0.2 to 0.5 part of water reducing agent, the solid waste-based cementing material comprises the following components in parts by mass: 40-70 parts of water-quenched slag powder, 10-30 parts of carbide slag, 10-20 parts of gypsum, 5-20 parts of fly ash and 0-5 parts of silica fume. By utilizing the internal curing effect of the titanium slag aggregate, continuous water can be provided for concrete hydration, the later-stage dry shrinkage of the concrete is reduced, and the strength of the concrete is improved; the high alkalinity of the carbide slag and the high sulfate content of the gypsum are utilized, and the alkali-sulfate synergistic excitation effect is utilized, so that the activity of the water-quenched slag powder and the like can be fully excited under the condition that cement and a chemical exciting agent are not used, and the strength performance of the concrete is ensured; meanwhile, steel slag is not used as a component material, so that the problem of poor concrete volume stability caused by the steel slag can be avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to a low-shrinkage all-solid waste concrete and a preparation method thereof. Background Art

[0002] With the proposal of the "carbon peak and carbon neutrality" goals, it is necessary and urgent to reduce carbon emissions from building materials. The most effective way to reduce carbon emissions from concrete materials is to reduce the amount of cement used and vigorously promote the resource utilization of solid waste materials. Without using cement, the use of all solid waste materials to prepare concrete and other building materials with better performance has significant environmental, economic and social benefits.

[0003] The annual output of high-titanium heavy slag exceeds 10 million tons, and the accumulated stockpiling exceeds 70 million tons. Its huge output has already affected the ecological environment safety. At the same time, due to its mineral composition, its volcanic ash activity is very low, and its resource utilization is very difficult. The current utilization method uses a small amount. As concrete aggregate, it can effectively achieve the reduction and resource utilization of high-titanium heavy slag. Titanium slag aggregate treated with water retention can play the role of "internal maintenance" in concrete, reduce the drying shrinkage of concrete, etc., and continuously provide the required water for the later hydration reaction of concrete, which is conducive to the continuous improvement of concrete strength. The reserves of calcium carbide slag are huge. At present, the stockpiling of calcium carbide slag in China has reached more than 10 million tons. The large-scale stockpiling of calcium carbide slag, on the one hand, its strong alkalinity will change the soil pH in the storage area and destroy the original soil quality; on the other hand, its accumulation will also lead to the enrichment of harmful trace elements, and long-term infiltration will cause groundwater pollution, affecting the living environment of surrounding residents. However, the strong alkalinity of calcium carbide slag can effectively stimulate the volcanic ash activity of materials such as mineral powder and fly ash, and can play the role of cement to a certain extent. The amount of industrial by-product gypsum is very huge, but because it contains certain impurities, it is difficult to use directly.

[0004] At the same time, the three essential core materials of clinker-free cementitious materials in solid waste-based concrete are mineral powder, steel slag powder and desulfurized gypsum. The use of steel slag may cause the problem of poor volume stability of concrete. At the same time, the preparation of concrete with solid waste-based cementitious materials usually requires a large amount of cementitious materials and a low water-cement ratio, which leads to large shrinkage of solid waste-based concrete. In addition, the current activation of the activity of solid waste-based materials usually involves adding chemical activators to concrete, which can lead to problems such as alkali reflux and frosting of the concrete.

[0005] In view of this, this application is hereby filed. Summary of the invention

[0006] In order to solve the problems of the above-mentioned prior art, the present invention provides a low-shrinkage all-solid waste concrete and a preparation method thereof, which utilizes the "internal curing" effect of titanium slag aggregate to provide continuous moisture for concrete hydration, reduce the late shrinkage of concrete and improve the strength of concrete; utilizes the high alkalinity of carbide slag and the high sulfate content of gypsum, and utilizes the alkali-sulfate synergistic excitation effect to fully stimulate the activity of water-quenched slag powder and the like to ensure the strength performance of concrete without using cement and chemical activators; and at the same time, does not use steel slag as a constituent material, which can avoid the problem of poor volume stability of concrete caused by steel slag.

[0007] The present invention is achieved through the following technical solutions:

[0008] In a first aspect, the present invention provides a low shrinkage all-solid waste concrete, comprising the following component raw materials in parts by weight:

[0009] 14-20 parts of solid waste-based cementitious materials, 25-40 parts of high-titanium heavy slag sand, 35-50 parts of high-titanium heavy slag crushed stone, 5.5-7.5 parts of water, and 0.2-0.5 parts of water reducing agent.

[0010] In a specific embodiment, the solid waste-based cementitious material includes the following components in parts by weight: 40 to 70 parts of water-quenched slag powder, 10 to 30 parts of carbide slag, 10 to 20 parts of gypsum, 5 to 20 parts of fly ash, and 0 to 5 parts of silica fume.

[0011] The present invention utilizes the "internal curing" effect of titanium slag aggregate to provide continuous moisture for concrete hydration, reduce the late shrinkage of concrete and improve the strength of concrete; utilizes the high alkalinity of carbide slag and the high sulfate content of gypsum, and utilizes the alkali-sulfate synergistic excitation effect to fully stimulate the activity of water-quenched slag powder and the like to ensure the strength performance of concrete without using cement and chemical activators; and at the same time, does not use steel slag as a constituent material, which can avoid the problem of poor volume stability of concrete caused by steel slag.

[0012] In a specific embodiment, the high-titanium heavy slag sand refers to the molten slag produced when vanadium-titanium magnetite is smelted into pig iron in a blast furnace, which is naturally cooled and then mechanically crushed and screened to obtain particles with a particle size of less than 4.75 mm.

[0013] In a specific embodiment, the high-titanium heavy slag crushed stone refers to the molten slag produced when vanadium-titanium magnetite is smelted into pig iron in a blast furnace, which is naturally cooled and then mechanically crushed and screened to obtain particles with a particle size of 4.75 to 31.5 mm.

[0014] The present invention uses saturated surface-dry titanium slag sand and gravel as aggregates, mainly because when preparing concrete with solid waste-based cementitious materials, the amount of cementitious materials used is usually large, resulting in large shrinkage of the concrete; titanium slag sand and gravel are hard and porous, and their internal moisture can be slowly released according to the relative humidity during the concrete hardening process to reduce the drying shrinkage of the concrete and provide the moisture required for continuous hydration of the cementitious material. Therefore, the present invention utilizes the "internal curing" effect of titanium slag aggregate to provide continuous moisture for concrete hydration, reduce the drying shrinkage of concrete, etc., which is beneficial to the continuous improvement of concrete strength. The strength can reach the C20 and C30 strength grade requirements, and can be suitable for roads and various non-load-bearing structural building materials.

[0015] The present invention adopts carbide slag as an alkaline activator and gypsum as a sulfate activator, taking into full consideration the synergistic activation of alkali + sulfate to activate the activity of materials such as slag; the strong alkalinity of carbide slag can effectively activate the volcanic ash activity of materials such as mineral powder and fly ash, and can play the role of cement to a certain extent; the sulfate content of industrial by-product gypsum is relatively high, and sulfate can not only activate the activity of slag but also react with the chemical composition of slag to produce more hydration products such as calcium aluminate to improve the performance of concrete. Therefore, the present invention utilizes the high alkalinity of carbide slag and the high sulfate content of gypsum, and utilizes the synergistic activation of alkali-sulfate, and can fully activate the activity of water-quenched slag powder and the like to ensure the strength performance of concrete without using cement and chemical activators.

[0016] The present invention uses fly ash mainly because the water demand of carbide slag is relatively large. The use of fly ash can reduce the water demand of concrete, improve the fluidity of concrete, and help reduce the water-binder ratio to increase the alkalinity of the solution in the concrete, thereby enhancing the excitation effect. Fly ash is also beneficial to improving the later strength of concrete.

[0017] The present invention uses a certain amount of silica fume, mainly because the concrete with a larger amount of mineral powder has a larger viscosity. The use of silica fume is beneficial to reducing the viscosity of the concrete, and can adjust the calcium-silicon ratio of the material composition, thereby improving the later strength of the concrete.

[0018] In a specific embodiment, the water-quenched slag powder refers to the powder obtained by grinding the siliceous calcium water-quenched slag with volcanic ash activity after smelting in a blast furnace or an electric furnace and then quenching and rapidly cooling.

[0019] In a specific embodiment, the water-quenched slag powder includes water-quenched blast furnace slag powder and / or water-quenched electric furnace phosphorus slag powder.

[0020] In a specific embodiment, the carbide slag is a strongly alkaline waste residue produced by hydrolysis of carbide in the process of industrial production of polyvinyl chloride, and the specific surface area obtained by drying and grinding is greater than 400m 2 / kg of powder material.

[0021] In a specific embodiment, the gypsum is desulfurized gypsum, phosphogypsum, fluorinated gypsum, titanium gypsum, or building gypsum prepared from industrial by-product gypsum.

[0022] In a second aspect, the present invention further provides a method for preparing low shrinkage all-solid waste concrete, comprising the following steps:

[0023] (1) Pre-wetting high-titanium heavy slag sand and high-titanium heavy slag crushed stone;

[0024] (2) Weighing high-titanium heavy slag sand and high-titanium heavy slag crushed stone in a saturated surface dry state, and weighing solid waste-based cementitious materials according to the composition ratio requirements, and pouring them into a mixer for stirring;

[0025] (3) Then, the water reducing agent and water are weighed according to a certain proportion, mixed, poured into a mixer and stirred evenly to obtain a low shrinkage all-solid waste concrete.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] 1. A low-shrinkage all-solid waste concrete and a preparation method thereof provided in an embodiment of the present invention utilizes the "internal curing" effect of titanium slag aggregate to provide continuous moisture for concrete hydration, reduce the late shrinkage of concrete and improve the strength of concrete; utilizes the high alkalinity of carbide slag and the high sulfate content of gypsum, and utilizes the alkali-sulfate synergistic excitation effect to fully stimulate the activity of water-quenched slag powder and the like to ensure the strength performance of concrete without using cement and chemical activators; and does not use steel slag as a constituent material, thereby avoiding the problem of poor volume stability of concrete caused by steel slag;

[0028] 2. A low-shrinkage all-solid waste concrete and a preparation method thereof provided in an embodiment of the present invention does not use steel slag as the main material. Compared with the current all-solid waste cementitious materials using steel slag as the core material, the volume stability problem caused by steel slag can be avoided;

[0029] 3. A low-shrinkage all-solid waste concrete and a preparation method thereof provided in an embodiment of the present invention utilizes the "internal curing" effect of titanium slag aggregate. Titanium slag sand and gravel are hard and porous. The internal moisture can be slowly released according to the relative humidity during the concrete hardening process to reduce the drying shrinkage of the concrete and provide the moisture required for the continuous hydration of the cementitious material. Therefore, the drying shrinkage of the concrete can be reduced, which is conducive to the continuous improvement of the strength of the concrete. The strength can reach the C20 and C30 strength grade requirements, and can be applied to roads and various non-load-bearing structural building materials;

[0030] 4. A low-shrinkage all-solid waste concrete and a preparation method thereof provided in an embodiment of the present invention give full play to the characteristics of the constituent materials, utilize the high alkalinity of solid waste material carbide slag and the high sulfate content of gypsum, and utilize the alkali-sulfate synergistic excitation effect, so as to fully stimulate the activity of water-quenched slag powder and the like to ensure the strength performance of concrete without using cement and chemical activators, and have the advantages of low carbon, green, good economy, etc., and can overcome the problems of large shrinkage, alkali return and blooming existing in traditional solid waste-based concrete and geopolymer concrete;

[0031] 5. The low-shrinkage all-solid waste concrete and its preparation method provided in the embodiments of the present invention can effectively realize the resource utilization of industrial solid waste into building materials, which is of great significance for the reduction and resource utilization of solid waste materials, and has good environmental, social and economic benefits. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0033] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, well-known materials or methods are not specifically described.

[0034] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0035] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0036] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0037] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0038] In a first aspect, an embodiment of the present invention provides a low-shrinkage all-solid waste concrete, including the following component raw materials in parts by weight:

[0039] 14-20 parts of solid waste-based cementitious materials, 25-40 parts of high-titanium heavy slag sand, 35-50 parts of high-titanium heavy slag crushed stone, 5.5-7.5 parts of water, and 0.2-0.5 parts of water reducing agent.

[0040] In a specific embodiment, the solid waste-based cementitious material includes the following components in parts by weight: 40 to 70 parts of water-quenched slag powder, 10 to 30 parts of carbide slag, 10 to 20 parts of gypsum, 5 to 20 parts of fly ash, and 0 to 5 parts of silica fume.

[0041] The present invention utilizes the "internal curing" effect of titanium slag aggregate to provide continuous moisture for concrete hydration, reduce the late shrinkage of concrete and improve the strength of concrete; utilizes the high alkalinity of carbide slag and the high sulfate content of gypsum, and utilizes the alkali-sulfate synergistic excitation effect to fully stimulate the activity of water-quenched slag powder and the like to ensure the strength performance of concrete without using cement and chemical activators; and at the same time, does not use steel slag as a constituent material, which can avoid the problem of poor volume stability of concrete caused by steel slag.

[0042] In a specific embodiment, the high-titanium heavy slag sand refers to the molten slag produced when vanadium-titanium magnetite is smelted into pig iron in a blast furnace, which is naturally cooled and then mechanically crushed and screened to obtain particles with a particle size of less than 4.75 mm.

[0043] In a specific embodiment, the high-titanium heavy slag crushed stone refers to the molten slag produced when vanadium-titanium magnetite is smelted into pig iron in a blast furnace, which is naturally cooled and then mechanically crushed and screened to obtain particles with a particle size of 4.75 to 31.5 mm.

[0044] The present invention uses saturated surface-dry titanium slag sand and gravel as aggregates, mainly because when preparing concrete with solid waste-based cementitious materials, the amount of cementitious materials used is usually large, resulting in large shrinkage of the concrete; titanium slag sand and gravel are hard and porous, and their internal moisture can be slowly released according to the relative humidity during the concrete hardening process to reduce the drying shrinkage of the concrete and provide the moisture required for continuous hydration of the cementitious material. Therefore, the present invention utilizes the "internal curing" effect of titanium slag aggregate to provide continuous moisture for concrete hydration, reduce the drying shrinkage of concrete, etc., which is beneficial to the continuous improvement of concrete strength. The strength can reach the C20 and C30 strength grade requirements, and can be suitable for roads and various non-load-bearing structural building materials.

[0045] The present invention adopts carbide slag as an alkaline activator and gypsum as a sulfate activator, taking into full consideration the synergistic activation of alkali + sulfate to activate the activity of materials such as slag; the strong alkalinity of carbide slag can effectively activate the volcanic ash activity of materials such as mineral powder and fly ash, and can play the role of cement to a certain extent; the sulfate content of industrial by-product gypsum is relatively high, and sulfate can not only activate the activity of slag but also react with the chemical composition of slag to produce more hydration products such as calcium aluminate to improve the performance of concrete. Therefore, the present invention utilizes the high alkalinity of carbide slag and the high sulfate content of gypsum, and utilizes the synergistic activation of alkali-sulfate, and can fully activate the activity of water-quenched slag powder and the like to ensure the strength performance of concrete without using cement and chemical activators.

[0046] The present invention uses fly ash mainly because the water demand of carbide slag is relatively large. The use of fly ash can reduce the water demand of concrete, improve the fluidity of concrete, and help reduce the water-binder ratio to increase the alkalinity of the solution in the concrete, thereby enhancing the excitation effect. Fly ash is also beneficial to improving the later strength of concrete.

[0047] The present invention uses a certain amount of silica fume, mainly because the concrete with a larger amount of mineral powder has a larger viscosity. The use of silica fume is beneficial to reducing the viscosity of the concrete, and can adjust the calcium-silicon ratio of the material composition, thereby improving the later strength of the concrete.

[0048] In a specific embodiment, the water-quenched slag powder refers to the powder obtained by grinding the siliceous calcium water-quenched slag with volcanic ash activity after smelting in a blast furnace or an electric furnace and then quenching and rapidly cooling.

[0049] In a specific embodiment, the water-quenched slag powder includes water-quenched blast furnace slag powder and / or water-quenched electric furnace phosphorus slag powder.

[0050] In a specific embodiment, the carbide slag is a strongly alkaline waste residue produced by hydrolysis of carbide in the process of industrial production of polyvinyl chloride, and the specific surface area obtained by drying and grinding is greater than 400m 2 / kg of powder material.

[0051] In a specific embodiment, the gypsum is desulfurized gypsum, phosphogypsum, fluorinated gypsum, titanium gypsum, or building gypsum prepared from industrial by-product gypsum.

[0052] In a second aspect, the present invention further provides a method for preparing low shrinkage all-solid waste concrete, comprising the following steps:

[0053] (1) Pre-wetting high-titanium heavy slag sand and high-titanium heavy slag crushed stone;

[0054] (2) Weighing high-titanium heavy slag sand and high-titanium heavy slag crushed stone in a saturated surface dry state, and weighing solid waste-based cementitious materials according to the composition ratio requirements, and pouring them into a mixer for stirring;

[0055] (3) Then, the water reducing agent and water are weighed according to a certain proportion, mixed, poured into a mixer and stirred evenly to obtain a low shrinkage all-solid waste concrete.

[0056] Example 1

[0057] The embodiment of the present invention provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 20% solid waste-based cementitious material, 29% high-titanium heavy slag sand, 44% high-titanium heavy slag crushed stone, 6.6% water, and 0.4% water reducer.

[0058] The cementitious material includes the following raw materials in parts by weight: 70% water-quenched blast furnace slag powder, 15% calcium carbide slag, 10% gypsum, 5% fly ash, and 0% silica fume.

[0059] The 28-day compressive strength of the all-solid waste concrete was 46.2MPa, and the 60-day compressive strength was 57.3MPa.

[0060] Example 2

[0061] The embodiment of the present invention provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 15% solid waste-based cementitious material, 36% high-titanium heavy slag sand, 42% high-titanium heavy slag crushed stone, 6.8% water, and 0.2% water reducer.

[0062] The cementitious material includes the following raw materials in parts by weight: 60% of water-quenched blast furnace slag powder, 20% of calcium carbide slag, 10% of gypsum, 8% of fly ash and 2% of silica fume.

[0063] The 28-day compressive strength of the all-solid waste concrete was 39.1 MPa, and the 60-day compressive strength was 48.2 MPa.

[0064] Example 3

[0065] The embodiment of the present invention provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 17% solid waste-based cementitious material, 33% high-titanium heavy slag sand, 43% high-titanium heavy slag crushed stone, 6.7% water, and 0.3% water reducer.

[0066] The cementitious material includes the following raw materials in parts by weight: 55% of water-quenched blast furnace slag powder, 20% of carbide slag, 10% of gypsum, 12% of fly ash and 3% of silica fume.

[0067] The 28-day compressive strength of the all-solid waste concrete was 34.6MPa, and the 60-day compressive strength was 45.2MPa.

[0068] Example 4

[0069] The embodiment of the present invention provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 17% solid waste-based cementitious material, 33% high-titanium heavy slag sand, 43% high-titanium heavy slag crushed stone, 6.7% water, and 0.3% water reducer.

[0070] The cementitious material includes the following raw materials in parts by weight: 40% water-quenched blast furnace slag powder, 20% calcium carbide slag, 20% gypsum, 20% fly ash, and 0% silica fume.

[0071] The 28-day compressive strength of the all-solid waste concrete was 32.3 MPa, and the 60-day compressive strength was 39.2 MPa.

[0072] Example 5

[0073] The embodiment of the present invention provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 17% solid waste-based cementitious material, 33% high-titanium heavy slag sand, 43% high-titanium heavy slag crushed stone, 6.7% water, and 0.3% water reducer.

[0074] The cementitious material includes the following raw materials in parts by weight: 40% water-quenched electric furnace phosphorus slag powder, 20% carbide slag, 20% gypsum, 20% fly ash, and 0% silica fume.

[0075] The 28-day compressive strength of the all-solid waste concrete was 30.1 MPa, and the 60-day compressive strength was 38.6 MPa.

[0076] Example 6

[0077] The embodiment of the present invention provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 17% solid waste-based cementitious material, 33% high-titanium heavy slag sand, 43% high-titanium heavy slag crushed stone, 6.7% water, and 0.3% water reducer.

[0078] The cementitious material includes the following raw materials in parts by weight: 70% of water-quenched electric furnace phosphorus slag powder, 15% of calcium carbide slag, 10% of gypsum, 5% of fly ash, and 0% of silica fume.

[0079] The 28-day compressive strength of the all-solid waste concrete was 44.9MPa, and the 60-day compressive strength was 55.2MPa.

[0080] Example 7

[0081] The embodiment of the present invention provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 14% solid waste-based cementitious material, 39% high-titanium heavy slag sand, 40% high-titanium heavy slag crushed stone, 6.7% water, and 0.3% water reducer.

[0082] The cementitious material includes the following raw materials in parts by weight: 65% of water-quenched blast furnace slag powder, 15% of calcium carbide slag, 10% of gypsum, 10% of fly ash, and 0% of silica fume.

[0083] The 28-day compressive strength of the all-solid waste concrete was 30.9 MPa, and the 60-day compressive strength was 41.2 MPa.

[0084] Example 8

[0085] The embodiment of the present invention provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 14% solid waste-based cementitious material, 39% high-titanium heavy slag sand, 40% high-titanium heavy slag crushed stone, 6.7% water, and 0.3% water reducer.

[0086] The cementitious material includes the following raw materials in parts by weight: 45% water-quenched blast furnace slag powder, 20% calcium carbide slag, 15% gypsum, 20% fly ash, and 0% silica fume.

[0087] The 28-day compressive strength of the all-solid waste concrete was 25.4 MPa, and the 60-day compressive strength was 32.2 MPa.

[0088] Comparative Example 1

[0089] This comparative example provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 20% solid waste-based cementitious material, 29% high-titanium heavy slag sand, 44% high-titanium heavy slag crushed stone, 6.6% water, and 0.4% water reducing agent.

[0090] The cementitious material includes the following raw materials in parts by weight: 35% of water-quenched blast furnace slag powder, 15% of calcium carbide slag, 10% of gypsum, 40% of fly ash, and 0% of silica fume.

[0091] The 28-day compressive strength of the all-solid waste concrete was 12.2 MPa, and the 60-day compressive strength was 18.1 MPa.

[0092] Comparative Example 2

[0093] This comparative example provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 20% solid waste-based cementitious material, 29% high-titanium heavy slag sand, 44% high-titanium heavy slag crushed stone, 6.6% water, and 0.4% water reducing agent.

[0094] The cementitious material includes the following raw materials in parts by weight: 35% water-quenched blast furnace slag powder, 35% calcium carbide slag, 10% gypsum, 20% fly ash, and 0% silica fume.

[0095] The 28-day compressive strength of the all-solid waste concrete is 14.5 MPa, and the 60-day compressive strength is 19.2 MPa.

[0096] Comparative Example 3

[0097] This comparative example provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 20% solid waste-based cementitious material, 29% high-titanium heavy slag sand, 44% high-titanium heavy slag crushed stone, 6.6% water, and 0.4% water reducing agent.

[0098] The cementitious material includes the following raw materials in parts by weight: 25% water-quenched blast furnace slag powder, 10% calcium carbide slag, 15% gypsum, 50% fly ash, and 0% silica fume.

[0099] The 28-day compressive strength of the all-solid waste concrete is 8.5 MPa, and the 60-day compressive strength is 14.3 MPa.

[0100] Comparative Example 4

[0101] This comparative example provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 20% solid waste-based cementitious material, 29% high-titanium heavy slag sand, 44% high-titanium heavy slag crushed stone, 6.6% water, and 0.4% water reducing agent.

[0102] The cementitious material includes the following raw materials in parts by weight: 30% water-quenched blast furnace slag powder, 30% carbide slag, 0% gypsum, 40% fly ash, and 0% silica fume.

[0103] The 28-day compressive strength of the all-solid waste concrete is 6.8 MPa, and the 60-day compressive strength is 10.4 MPa.

[0104] Comparative Example 5

[0105] This comparative example provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 20% solid waste-based cementitious material, 29% high-titanium heavy slag sand, 44% high-titanium heavy slag crushed stone, 6.6% water, and 0.4% water reducing agent.

[0106] The cementitious material includes the following raw materials in parts by weight: 50% water-quenched blast furnace slag powder, 0% calcium carbide slag, 0% gypsum, 40% fly ash, and 10% silica fume.

[0107] The 28-day compressive strength of the all-solid waste concrete was 0.8 MPa, and the 60-day compressive strength was 1.0 MPa.

[0108] Comparative Example 6

[0109] The embodiment of the present invention provides a low-shrinkage all-solid waste concrete, comprising the following raw materials in parts by weight: 14% solid waste-based cementitious material, 39% limestone machine-made sand, 40% limestone crushed stone, 6.7% water, and 0.3% water reducer.

[0110] The cementitious material includes the following raw materials in parts by weight: 65% of water-quenched blast furnace slag powder, 15% of calcium carbide slag, 10% of gypsum, 10% of fly ash, and 0% of silica fume.

[0111] The 28-day compressive strength of the all-solid waste concrete was 30.9 MPa, and the 60-day compressive strength was 37.8 MPa.

[0112] From the above results, it can be seen from comparative examples 1 to 4 that: when the proportion of water-quenched slag powder in the solid waste-based cementitious material is less than 40%, the concrete strength of embodiments 1 to 8 that meet the requirements of the present invention is significantly reduced; it can be seen from comparative examples 4 and 5 that: the strength of concrete without using carbide slag or gypsum is very low, and the concrete without using carbide slag and gypsum at the same time has almost no strength; it can be seen from comparative example 6 and embodiment 7 that: the increase in the 60-day strength of concrete using ordinary limestone aggregate relative to the 28-day strength is less than that of concrete using high-titanium heavy slag sand and high-titanium heavy slag crushed stone as aggregate.

[0113] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A low shrinkage all-solid waste concrete, characterized in that: The components include the following mass parts: 14-20 parts of solid waste-based cementitious materials, 25-40 parts of high-titanium heavy slag sand, 35-50 parts of high-titanium heavy slag crushed stone, 5.5-7.5 parts of water, and 0.2-0.5 parts of water reducing agent.

2. The low shrinkage all-solid waste concrete according to claim 1, characterized in that: The solid waste-based cementitious material comprises the following components in parts by weight: 40 to 70 parts of water-quenched slag powder, 10 to 30 parts of carbide slag, 10 to 20 parts of gypsum, 5 to 20 parts of fly ash, and 0 to 5 parts of silica fume.

3. The low shrinkage all-solid waste concrete according to claim 1, characterized in that: The high-titanium heavy slag sand refers to the molten slag produced when vanadium-titanium magnetite is smelted into pig iron in a blast furnace. After natural cooling, it is mechanically crushed and screened to obtain particles with a particle size of less than 4.75 mm.

4. The low shrinkage all-solid waste concrete according to claim 1, characterized in that: The high-titanium heavy slag crushed stone refers to the molten slag produced when vanadium-titanium magnetite is smelted into pig iron in a blast furnace. After natural cooling, it is mechanically crushed and screened to obtain particles with a particle size of 4.75 to 31.5 mm.

5. The low shrinkage all-solid waste concrete according to claim 1, characterized in that: The water-quenched slag powder refers to the powder obtained by grinding the calcium-silicon water-quenched slag with volcanic ash activity after smelting in a blast furnace or an electric furnace and then quenching and rapidly cooling the slag with water.

6. The low shrinkage all-solid waste concrete according to claim 5, characterized in that: The water-quenched slag powder includes water-quenched blast furnace slag powder and / or water-quenched electric furnace phosphorus slag powder.

7. The low shrinkage all-solid waste concrete according to claim 1, characterized in that: The carbide slag is a powder material obtained by drying and grinding the strongly alkaline waste residue produced by the hydrolysis of carbide in the process of industrial production of polyvinyl chloride.

8. The low shrinkage all-solid waste concrete according to claim 7, characterized in that: The specific surface area of ​​the powder material is greater than 400m 2 / kg.

9. The low shrinkage all-solid waste concrete according to claim 1, characterized in that: The gypsum is desulfurized gypsum, phosphogypsum, fluorinated gypsum, titanium gypsum, or building gypsum prepared from industrial by-product gypsum.

10. The method for preparing low shrinkage all-solid waste concrete according to any one of claims 1 to 9, characterized in that: The steps include: (1) Pre-wetting high-titanium heavy slag sand and high-titanium heavy slag crushed stone; (2) Weighing high-titanium heavy slag sand and high-titanium heavy slag crushed stone in a saturated surface dry state, and weighing solid waste-based cementitious materials according to the composition ratio requirements, and pouring them into a mixer for stirring; (3) Then, the water reducing agent and water are weighed according to a certain proportion, mixed, poured into a mixer and stirred evenly to obtain a low shrinkage all-solid waste concrete.

Citation Information

Cited By

  • Early-strength anti-cracking negative carbon type cement stabilized soil as well as preparation method and application thereof

    CN120247517A

  • An early-strength, crack-resistant, negative-carbon cement-stabilized soil and its preparation method and application

    CN120247517B

  • All-solid waste mining functional cementing material, preparation method and application

    CN120647186A

  • Fly ash-based geopolymer concrete and preparation method thereof

    CN120943569A

  • Steam-curing-free quick-hardening early-strength solid waste-based foam concrete and preparation method thereof

    CN122102649A